UNVEILING MISCONCEPTIONS IN SCHOOL COUNSELING: EXPLORING STUDENT PERCEPTIONS AND CHALLENGES IN GUIDANCE SERVICES IMPLEMENTATION - Mahaly, Sawal; Hariko, Rezki; Syawaluddin; Makatita, Triandini (CV. TOTUS TUUS, 2025)
Guidance and counseling services play a crucial role in student development, yet misconceptions about their implementation persist. This study aimed to examine students' knowledge and misunderstandings regarding counseling services in schools, focusing on their perceptions of counseling roles and effectiveness. Using a quantitative descriptive approach, data were collected from 62 students of the FKIP Counseling Guidance Program at Pattimura University through a structured questionnaire. The results revealed significant misconceptions, with 75.81% of students believing that counseling is merely giving advice, 77.42% perceiving it as limited to certain students, and 74.19% viewing school counselors as